(untitled) (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2026)
Rubber plants are a very important plantation commodity in Indonesia, rubber plants provide a significant contribution as a supplier of rubber raw materials and play an important role in environmental conservation and biological resources. Rubber plants produce latex, to improve the quality of latex, improvements that can be made are by using grafted seeds. Therefore, in cultivating rubber plants, good planting materials are needed to support the productivity of rubber plants. To increase latex production in rubber plants, stimulant treatment is needed. This study aims to determine the effect of providing organic stimulants from avocado (Persea americana Mill) fruit peels on the latex yield of clone PB 260 and to obtain the best concentration results from providing organic stimulants from avocado (Persea americana Mill) fruit peels. The method used is a randomized block design (RAK) consisting of one treatment factor, namely the concentration of ethrel and the concentration of avocado peel extract consisting of 6 treatment levels. A0 = Without Stimulant, A1 = Ethrel 10pa Concentration 2.5%, A2 = Avocado Peel Extract Concentration 50 gr/300ml, A3 = Avocado Peel Extract Concentration 100 gr/300ml, A4 = Avocado Peel Extract Concentration 150 gr/300ml, A5 = Avocado Peel Extract Concentration 200 gr/300ml. Each treatment had 4 repetitions, so there were 24 experimental plants.